2015
DOI: 10.1016/j.jcin.2014.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Ultrasound Guidance Facilitates Transradial Access

Abstract: Ultrasound guidance improves the success and efficiency of radial artery cannulation in patients presenting for transradial catheterization. (Radial Artery Access With Ultrasound Trial [RAUST]; NCT01605292).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(73 citation statements)
references
References 19 publications
3
66
1
3
Order By: Relevance
“…5,14,20 The application of subcutaneous nitrates and the implementation of ultrasound-guided puncture may facilitate radial artery cannulation and reduce the number of puncture attempts needed to achieve cannulation. 21,22 In addition, we also observed a negative correlation between radial lumen at 30 days and the number of puncture attempts. This might have important consequences for future catheterizations through the same radial access considering that smaller and less pulsatile arteries might be more difficult to cannulate.…”
Section: Discussionsupporting
confidence: 57%
“…5,14,20 The application of subcutaneous nitrates and the implementation of ultrasound-guided puncture may facilitate radial artery cannulation and reduce the number of puncture attempts needed to achieve cannulation. 21,22 In addition, we also observed a negative correlation between radial lumen at 30 days and the number of puncture attempts. This might have important consequences for future catheterizations through the same radial access considering that smaller and less pulsatile arteries might be more difficult to cannulate.…”
Section: Discussionsupporting
confidence: 57%
“…Because there was no previous study on the effect of simulation training in ultrasound-guided radial artery cannulation, sample size was calculated based on the previously reported first attempt success rate in ultrasound-guided radial artery cannulation. The first attempt success rate was 65% in a previous study, [17] while a pilot study in our center involving only novices in ultrasound-guided radial artery cannulation had a first attempt success rate of 35%. Assuming a difference in means of 30% in first attempt success rate between the simulation group and the control group, the necessary minimum sample size PLOS ONE to achieve the desired power of 0.8 and alpha error of 0.05 was 80 artery cannulations (40 per group).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, multiple studies have shown that the radial artery can be easily identified via ultrasound 6,8,9. We attempted to show that noninvasive peripheral arterial BP could be similarly assessed using common items found in most EDs.…”
Section: Discussionmentioning
confidence: 99%